IMPLEMENTASI LEAN ACCOUNTING PADA PERUSAHAAN INDUSTRI - Kanivia, Aan; Supriyadi, Agung; Putrie, Nidzma Adelia; Puspita, Baby Bernadetha (Fakultas Ekonomi dan Bisnis, 2024)
The traditional accounting system that can no longer adjust to the industrial company system encourages the birth of lean accounting. Lean accounting is an approach created to support the development of lean manufacturing by using systems and methods created based on lean principles, namely Visual Performance Measurement, Continuous Improvement (CI), Value Stream Costing, and Target Costing. The writing of this article aims to find out how the implementation of lean accounting in industrial companies. The method used in this research is the literature study method. The results of this study state that the implementation of lean accounting in industrial companies has a positive impact on company performance so that companies can save costs, reduce waste, improve operational efficiency, and help companies make the right decisions with accurate information.Key words: Lean accounting, Visual Performance Measurement, Continuous Improvement (CI), Value Stream Costing, and Target Costing.